Journalists in the zone of armed conflicts: the need to respect international humanitarian law / Azlena Khalid - Khalid, Azlena (Centre for Media and Information Warfare Studies, 2008)
Journalists and media personnel while engaged in dangerous professional missions in areas of armed conflict or in similar situations constantly face risks and are at times subjected to deliberate attacks. In such situations, provided that they do not partake in direct hostilities, they are civilians that share the rights and duties of any member of the civilian population and deserve the protection given unto them within the rules of international humanitarian law. Thus, renewed attention should be given by States and non-State actors on the responsibility to protect journalists and media personnel in the zones of armed conflict and to remind all parties in armed conflict of the need to ensure respect for the professional independence of journalists and media personnel. This responsibility encompasses the need to ensure respect for international humanitarian law during armed conflict which must then be translated into affirmative and collective action on the part of the State and non-State actors so that journalists and media personnel can enjoy the protection accrued to them under applicable international law and international humanitarian law. The Governments concerned must face up to this responsibility and accordingly encouraged by the international community to assume their responsibilities and not to shirk them.